A comprehensive quality evaluation of Fuzi and its processed product through integration of UPLC-QTOF/MS combined MS/MS-based mass spectral molecular networking with multivariate statistical analysis and HPLC-MS/MS. (10th February 2021) - Lei, Huibo; Zhang, Yuhao; Ye, Ji; Cheng, Taofang; Liang, Yanlin; Zu, Xianpeng; Zhang, Weidong
Abstract: Ethnopharmacological relevance: Aconiti Lateralis Radix Praeparata (the Chinese name is Fuzi, FZ), the lateral or daughter root of Aconitum carmichaelii Debx . (Ranunculaceae), is a controversial traditional Chinese medicine (TCM) that is universally distributed and applied in many countries, such as China, Japan, Korea, and India. FZ can be used to treat various diseases, including rheumatic fever, rheumatism, painful joints, syncope, collapse, bronchial asthma, some endocrinal disorders, etc . However, quality control and assessment of FZ are challenging due to its obvious and high toxicological risks, and only its processed products are allowed to be used clinically according to the relative safety regulations. Consequently, it is necessary to analyze the whole chemical composition and the dynamic changes of FZ before and after processing. Addressing the changes in the chemical substance of raw and processed products is a way to reduce toxicity. Aim of the study: In this article, the whole chemical composition of FZ is analyzed, the differences between raw and processed FZ are evaluated, and possible factors that influence the reduced toxicity of processed FZ are explained from the perspective of its chemical composition using qualitative and quantitative analysis methods. Materials and methods: A novel strategy of multiple data collection and processing based on ultra-performance liquid chromatography coupled with a quadrupole time-of-flight mass spectrometry (UPLC-QTOF/MS) method in the positive ion mode, together with Global Natural Product Social Molecular Networking (GNPS) and multivariate statistical analysis, was established to systematically identify the chemical constituents of FZ and comprehensively investigate the chemical markers that can be used to differentiate FZ processed with vinegar and honey from its raw product. Combined with the qualitative analysis results, 12 components, including 8 chemical marker compounds and 4 toxicity components, were quantitatively analyzed by using high-performance liquid chromatography equipped with triple-quadrupole mass spectrometry (HPLC-MS/MS). Results: Using the molecular networking (MN) analysis method, a total of 145 compounds were identified, of which 13 were identified using reference compounds. Seventy seven chemical markers were also detected between raw and processed FZ. The identification results of the chemical markers were also verified by orthogonal partial least squares discriminant analysis (OPLS-DA). The quantitative results indicated that the contents of 12 important components all decreased, especially diester-diterpenoid alkaloids (DDAs), after processing. Conclusion: The decrease of toxicity of FZ after processing is closely related to the changes in its chemical composition. The method developed in this study is a comprehensive analysis technique for quality assessment of FZ, and this study provides a useful and quick strategy to characterize chemical compounds of TCM and explore the different chemical markers between raw and processed Chinese herbal medicine. Graphical abstract: Image 1